Assessment of different traditional techniques of storing harvested corms of tannia (xanthosoma sagitifollia) and taro (colocasia esculenta) varieties - Mugumo, Nyikahadzoi (Midlands State University, 2017)
An experiment on the effect of different storage techniques on taro and tannia corms was carried out in a 2x5 factorial in a complete block design(CBD) replicated three times. Taro and tannia crops and the factors are different storage techniques. The techniques include refrigeration, heap covered with maize stalks, ash smeared corms, pit storage and corms stored under room temperature conditions. Taro and tannia corms were stored for 18 weeks after being cured using the same technique for 2 weeks. Then data on weight loss, pest damage, and corm rot and sprouting was measured. There was no significant differences (P>0.001) on the number of corms that were affected by pest during storage time. The corm weight was significantly different (P<0.001). There was a significant difference in the number of sprouted corms between taro and tannia corms (P < 0.001). This study concludes that refrigeration technique had less rots, less sprouting and no pest damage. The corms that were stored in pit lost less weight as compared to all other techniques. Farmers can use the pit method to store harvested corms if there are not bruised at harvesting